The issue context of modern American politics: Semiparametric identification of latent factors from discrete data - Byron Schafer; Richard Henry Spady (Centre for Microdata Methods and Practice (cemmap), 2002)
A new methodology that estimates attitudes semiparametrically and estimates actions nonparametrically, as a function of the resulting attitudinal measures, is used to examine the behavioral effects of ѣultural' and conomic' preferences in the Presidential elections of 1984 and 1992. The results suggest a shift toward ѣultural politics achieved Ųst among the highly educated but spreading throughout society by the later election. One consequence is that both parties are now consistent in their policy alignments״he Democrats being liberal on both scales, the Republicans conservative. Despite this aggregate consistency, different social groups are attached to the parties in diĥrent ways, thereby heightening the potential for intraparty conǩct while sharpening the problem of fashioning a platform that is broadly attractive. These problems, finally, express themselves very diĥrently within the Democratic and the Republican parties.
Keywords: 330; Präsidentschaftswahl; Wahlverhalten; Nichtparametrisches Verfahren; USA